The Existence of Community Culture in the Framework of Mappanretasi Local Wisdom in Tanah Bumbu Regency - Didi Susanto; Rico Rico; Muzahid Akbar Hayat (STMIK Dharma Wacana, 2024)
The Mappanretasi tradition is a form of local wisdom of the Bugis people in Tanah Bumbu Regency, South Kalimantan, which has spiritual, social, and economic meanings. This research aims to inventory the cultural elements of Mappanretasi, analyze its impact on the Micro, Small, and Medium Enterprises (MSMEs) sector, and identify challenges in preserving this tradition. This study uses a qualitative approach with phenomenological design. Data were collected through in-depth interviews, participatory observations, and documentation studies, involving indigenous leaders, local communities, and local governments. The results of the study show that Mappanretasi reflects the relationship between humans and nature through symbols such as ritual boats and offerings of marine products, which symbolize gratitude and community solidarity. This tradition also has a significant economic impact, especially for MSMEs in the culinary, handicrafts, and service sectors, with a surge in demand for local products during its implementation. However, the preservation of this tradition faces challenges such as declining interest among younger generations, lack of formal documentation, and modernization pressures that have the potential to diminish the spiritual essence of the tradition. This research suggests formal documentation of traditions through digitalization, integration of cultural values into formal education, and collaboration between governments, communities, and the private sector to address these challenges. With a strategic and holistic approach, the Mappanretasi tradition can continue to be an integral part of local cultural identity while supporting sustainable economic development